SOLUTION EFFORTS TO OVERCOME DIFFICULTIES IN LEARNING TADFIDZ AL-QUR`AN AT SCHOOL - Nanang Faisol Hadi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research was based on the number of children who had difficulties when learning took place, disturbed their friends when learning and there were some children who did not want to follow the tahfiz learning well. This research aims to find out how the teacher's solution activities are in overcoming difficulties in learning tahfiz Al-Qur'an. The subjects of this research were Islamic Religious Education teachers and 4 homeroom teachers at SMPN 27 PPU. while the object of this research is the activities of PAI teachers in overcoming difficulties in learning tahfiz and the factors that influence teachers' efforts to overcome students' difficulties in learning tahfiz at SMPN 27 PPU. The data collection techniques used in this research are observation, interview and documentation techniques. Next, it is presented qualitatively descriptively in the form of descriptions. From the results of this research, it emerged that the teacher's solution activities in overcoming difficulties in learning tahfiz Al-Qur'an were by collecting data, processing data, diagnosis, prognosis, treatment and evaluation. Meanwhile, the factors that influence teacher efforts are student interests, teacher educational background and experience, family media, and school.